THE IMPACT OF INTERNAL CONTROL ON THE QUALITY OF ACCOUNTING INFORMATION SYSTEMS-AN EMPIRICAL STUDY ON ELECTRIC INDUSTRY COMPANIES IN THE REPUBLIC OF IRAQ - Sajjad Mohammed Ali; Lassaad Lakhal; Enas Abbas Abed (Scholars Digest Publishing, 2024)
The research aims to determine the extent of the impact of Internal Control on the Quality of Accounting Information Systems in electric industry companies in the Republic of Iraq. The study utilized a descriptive-analytical research method, with the research population consisting of employees in electric industry companies within the Republic of Iraq. The research sample size was 357 individuals. The research findings concluded that there is a statistically significant relationship between Internal Control and the Quality of Accounting Information Systems in electric industry companies within the Republic of Iraq. As a result, the research recommends the Enhance Internal Control Mechanisms and relevant operations and Prioritize Risk Assessment.
Keywords: Quality of Accounting Information Systems, The Regulatory Environment, Control Activities, Electric Industry Companies.